RESPON ISLAM TERHADAP PERUBAHAN RELASI MASYARAKAT LOKAL DAN NEGARA DI INDONESIA ERA REFORMASI - Muntoha Muntoha (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2015)
AbstractIndonesia as a developing country starts moving from the centralistic country into decentralized state since the change of power generated by a wave of reforms in mid 1998. There are several key issues that came to the surface in connection with this transition, among others, is a horizontal conflict that is lead to the disintegration of the Republic of Indonesia (NKRI). In the face of the country situation, the religion (Islam) with the teaching of ethics is expected to be one important factor for the integration process, especially Islam embraced the majority of the Indonesian population. In the study presented formulation of the problem of how the contribution of Islam in the context of the local communities to build relationships and state in Indonesia after the collapse of the New Order regime more equitably? The result of this study has been revealed that the contribution of Islam through the base organization at least can be categorized  into three, namely NU, Muhammadiyah, HTI, and MMI. As for the contribution of ideas from NU and Muhammadiyah, that the local community and state relations should be seen in terms of the ideology of Pancasila as the noble nation and agreement of the founders of the nation. Then from HTI, to make the relationship with the local society can be run with a harmonious state is the first system to change the leadership of the country into a caliphate. Furthermore, from the MMI, suggesting if the pattern of the relationship between local communities and the state can run well, then the state must be firm by making Islamic law as its legal basis. It is based on the premise that in Islamic law are values as true and when implemented can provide prosperity for humankind. Keywords: relasi, Islam, masyarakat lokal, dan kontribusi